1999
DOI: 10.1007/s002770050510
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatitis B flare-up during chemotherapy using lamivudine: case report and review of the literature

Abstract: Reactivation of chronic hepatitis B in patients receiving cytotoxic treatment for non-Hodgkin's lymphoma is well documented. We report a case of a patient with chronic hepatitis B who was treated by chemotherapy because of non-Hodgkin's lymphoma. After the second cycle of chemotherapy she developed a severe flare-up of hepatitis B. Liver biopsy revealed highly active hepatitis and confluent necroses. Within 3 weeks, the patient recovered spontaneously. Prophylactic treatment with lamivudine (Epivir,Glaxo-Wellc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 18 publications
1
40
1
2
Order By: Relevance
“…95 Lamivudine has also been claimed to be effective in controlling viral replication during HBV reactivation, 79,101,102 thereby allowing individual patients to continue cytotoxic chemotherapy upon maintenance of a sufficient hepatic function. 102,103 Sustained HBeAg seroconversion and undetectable serum HBV DNA level for at least 3 months after the discontinuation of lamivudine therapy have also been observed in some patients who were initially HBeAg-seropositive, 103 and the postulated mechanism has been a high immune response to HBV reactivation that allows elimination of covalently closed circular DNA in hepatocytes in conjunction with suppression of viral replication. Lamivudine has also been reported to be effective in cases of hepatic decompensation during HBV reactivation 94,104 and in cases that involve a precore HBV mutant.…”
Section: Management Of Established Hbv Reactivationmentioning
confidence: 99%
“…95 Lamivudine has also been claimed to be effective in controlling viral replication during HBV reactivation, 79,101,102 thereby allowing individual patients to continue cytotoxic chemotherapy upon maintenance of a sufficient hepatic function. 102,103 Sustained HBeAg seroconversion and undetectable serum HBV DNA level for at least 3 months after the discontinuation of lamivudine therapy have also been observed in some patients who were initially HBeAg-seropositive, 103 and the postulated mechanism has been a high immune response to HBV reactivation that allows elimination of covalently closed circular DNA in hepatocytes in conjunction with suppression of viral replication. Lamivudine has also been reported to be effective in cases of hepatic decompensation during HBV reactivation 94,104 and in cases that involve a precore HBV mutant.…”
Section: Management Of Established Hbv Reactivationmentioning
confidence: 99%
“…A series of patients receiving immunosuppression for bone marrow transplant demonstrated markedly low rates of reactivation without adverse effects of prophylaxis with lamivudine. 41,[65][66][67] The first case series of primary prophylaxis was published in 2001 involving 20 patients with haematological malignancies and a variety of chemotherapy regimens, the majority of which also included glucocorticoids. 42 With a rate of HBV reactivation of 5%, the role of lamivudine for prophylaxis among HBsAg carriers appeared to be indicated.…”
Section: Hbv Reactivationmentioning
confidence: 99%
“…61,87 As expected, when lamivudine was used as prophylaxis rather than for treatment of HBV, it also displayed a benign side effect profile. 31,42,44,47,65,76,79 A major clinical concern regarding prophylactic therapy with lamivudine, and an area of substantial controversy, is development of lamivudine-resistant mutant strains of HBV. 58,68,88 Evidence originally was based on case series of HBV infection treated with lamivudine for >1 year.…”
Section: 10mentioning
confidence: 99%
“…Administration of lamivudine to the donor before the bone marrow harvest may be the easiest way to reduce HBV in harvested marrow; however, there may be a high risk of a rebound increase in HBV after cessation of lamivudine. 8,9 Since it is still uncertain how long the treatment should be maintained, it is better not to administer lamivudine to an HBVpositive carrier in order to avoid a possible rebound effect. Therefore, in vivo purging with lamivudine in the host after transplantation may be ethically the best way to eradicate HBV.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several studies have shown the effectiveness of lamivudine for inhibition of HBV reactivation and for clinical and pathological improvement in hepatic dysfunction even in patients with hematological diseases after stem cell transplantation. 7,8 Here, we report a successful allogeneic BMT from an HBV-positive sibling donor (HBV carrier) into a patient with severe aplastic anemia complicated by chronic hepatitis B, using lamivudine. …”
mentioning
confidence: 99%